Steric and electronic effect of secondary phosphines in reactions with cyclopalladated complexes. (1st February 2019) - Kukowski, Jonathan E.; Smoliakova, Irina P.
Graphical abstract: Reactions of chloro-bridged dimeric C, N -cyclopalladated complexes with secondary phosphines are sensitive to the molar ratio of the reagents, base presence, solvent, time and temperature and provide either aminophosphines (or other N, P ligands), mononuclear HPR2 adducts or mono-chloro, monophosphido-bridged dimeric C, N -cyclopalladated complexes as major products. Abstract: Reactions of secondary phosphines HPR 1 R 2 [R 1  = R 2  =  p -MeOC6 H4 (b ), p -CF3 C6 H4 (c ), mesityl (Mes, d ) or 1-adamantyl (Ad, e ); R 1  =  t -Bu, R 2  = Ph (f )] with cyclopalladated complexes (CPCs) derived from N, N -dimethylbenzylamine (1 ), l -fenchone methyloxime (3 ), ( S )- N, N -dimethylbenzylamine (9 ), and ( S )-di-2, 4- tert -butyloxazoline (11 ) were studied. Phosphination of the cyclopalladated ligands in complexes1 and3 was observed using either 4.5:1 or 9:1 molar ratios of HPAr2 (b, c ) to CPC in the presence of 9 equiv. Cs2 CO3 . The corresponding N, P ligands2b, c and4b, c were isolated in 44–59% yields. Reactions of the sterically hindered HPMes2 with CPCs1 and3 provided the phosphination product, 4d′, only for the latter complex (32% yield). Attempts to synthesize N, P ligands with HPAd2 were unsuccessful with either palladacycle. Major products of the reactions of complexes1 and3 with bulky HPMes2 and HPAd2 were either rare mononuclear complexes5d, e (up to 90%) and7d, e (81 and 86%) with an ancillary secondary phosphine ligand or dinuclear monophosphido, monochloro-bridged complexes6d (98%) and8d, e (69% and 66%) depending on the HPR2 :CPC molar ratio used. Enantiopure CPC3 reacted with racemic HP t -BuPh to give a single diastereomer of the phosphination product4f in 12% yield. Attempts to use the racemic phosphine in transformations with two other enantiopure CPCs, 9 and11, to form a CP t -BuPh bond were unsuccessful. Instead, reactions of these two complexes with racemic HP t -BuPh provided monophosphido, monochloro-bridged CPCs11f and13f in 32 and 76% yield, respectively. Analysis of 1 H, 13 C{ 1 H} and 31 P{ 1 H} NMR data of all new Pd(II) complexes and N, P ligands is provided. An X-ray crystallographic study of complex7d proved its trans- N, P geometry.